Modern Determinants of the Vocational Education - KIEŁBASA, Marzena; NOGA, Henryk; MIGO, Piotr (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2015)
New education goals, a new teaching content requires from a teacher application of other, also more active teaching methods, and from students require a lot of commitment and increased independence. This paper shows selected conditions of vocational education, paying attention to the needs of acquiring new skills and the need for classification of occupations.